Formation of an Effective System of Financing the Innovative Activities of Enterprises (Eurasian Journal of History, Geography and Economics, 2022)
The article creating a positive investment climate should not be interpreted as a key process in the globalization of the economy, and as a result, the expansion of access to investment resources, which in turn will increase competition among investors. If we want to increase the volume of foreign investment, it is necessary to increase the investment potential of enterprises, regional conditions and conditions to a more acceptable and higher level than others (competitors), as well as to stimulate domestic (national) investment. we need to focus on ensuring that it is holistic.